2000
DOI: 10.1093/ajcn/72.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Body composition in children with celiac disease and the effects of a gluten-free diet: a prospective case-control study

Abstract: Background: Celiac disease is the most common cause of malnutrition in children of Western countries. Objective: The objective was to measure body composition in children at the time celiac disease was diagnosed and after consumption of a gluten-free diet (GFD). Design: We assessed body composition by dual-energy X-ray absorptiometry in 29 children and adolescents with a mean (± SD) age of 9.5 ± 3.4 y at the time celiac disease was diagnosed and in a subset of 20 patients after 1.2 ± 0.2 y of a GFD. We also st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
78
1
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 21 publications
7
78
1
7
Order By: Relevance
“…However, the authors did not characterize the symptoms of their patients, and the celiac and control groups were not matched for age, sex, or pubertal status. A follow-up study (21) by the same investigative group found a 19% decrease in total body bone mineral content (assessed by dual-energy X-ray absorptiometry) in a heterogeneous group of celiac children and adolescents that included patients with symptomatic disease.…”
Section: The Case For Screening-michael Freemarkmentioning
confidence: 99%
“…However, the authors did not characterize the symptoms of their patients, and the celiac and control groups were not matched for age, sex, or pubertal status. A follow-up study (21) by the same investigative group found a 19% decrease in total body bone mineral content (assessed by dual-energy X-ray absorptiometry) in a heterogeneous group of celiac children and adolescents that included patients with symptomatic disease.…”
Section: The Case For Screening-michael Freemarkmentioning
confidence: 99%
“…20 In general, patients who follow a gluten-free diet without straying from it recover their BMD more rapidly, but simply complying with the diet does not ensure normalization, even after years. 2,5,8,[19][20][21]25,[30][31][32][33] As is seen among chronic diseases in which dietary treatment is required, there is no guarantee that a gluten-free diet will be followed strictly over the long term, and failure to adhere to the diet was confirmed in 13 of our patients. 30 Serological tests for celiac disease have been recommended as an indirect measurement for monitoring the compliance with the diet.…”
Section: Discussionmentioning
confidence: 99%
“…GFD improves symptomology, reduces mucosal damage and eliminates risks for osteoporosis and bowel cancers associated with long term active CD [50][51][52][53][54][55][56]. All newly diagnosed patients should undergo a formal investigation for micronutrient deficiencies including serum iron, folic acid, vitamin D and vitamin B12 [40].…”
Section: Management Of Celiac Diseasementioning
confidence: 99%